Relationship of Romantic Beliefs on Marital Adjustment in Ta’aruf Individuals - Devianti; Maslihah, Sri; Nurendah, Gemala (Universitas Islam Indonesia, 2024)
For individuals who undergo ta'aruf, marriage adjustment is considered very important. One of the factors affecting marriage adjustment is romantic beliefs about marriage, which can lead to inconsistencies in marital relationships. This risk increases because the short time of ta'aruf acquaintance makes it difficult for people to interact early in the marriage. The study aims to find out how romantic beliefs about marriage affect marriage adjustment in married couples through the ta'aruf process. The study uses a quantitative approach with a correlational design. The research sample consisted of 98 individuals who were married through ta'aruf (with a marriage age range of 3-13 years). Research data were collected using the Relationship Beliefs Inventory (RBI) questionnaire, and the Revised Dyadic Adjustment Scale (RDAS) questionnaire. Data were analyzed using simple regression analysis. Research finds that romantic beliefs about marriage correlate negatively to marital adjustments. Individuals who have romantic beliefs on marriage have a tendency to resolve conflicts poorly and avoid speaking in person, which makes it harder for them to adjust to marriage.